Activin-A is overexpressed in severe asthma and is implicated in angiogenic processes. Issue 3 (12th February 2016) - Samitas, Konstantinos; Poulos, Nikolaos; Semitekolou, Maria; Morianos, Ioannis; Tousa, Sofia; Economidou, Erasmia; Robinson, Douglas S.; Kariyawasam, Harsha H.; Zervas, Eleftherios; Corrigan, Christopher J.; Ying, Sun; Xanthou, Georgina; et al.
Activin-A is a pleiotropic cytokine that regulates allergic inflammation. Its role in the regulation of angiogenesis, a key feature of airways remodelling in asthma, remains unexplored. Our objective was to investigate the expression of activin-A in asthma and its effects on angiogenesis in vitro . Expression of soluble/immunoreactive activin-A and its receptors was measured in serum, bronchoalveolar lavage fluid (BALF) and endobronchial biopsies from 16 healthy controls, 19 patients with mild/moderate asthma and 22 severely asthmatic patients. In vitro effects of activin-A on baseline and vascular endothelial growth factor (VEGF)-induced human endothelial cell angiogenesis, signalling and cytokine release were compared with BALF concentrations of these cytokines in vivo . Activin-A expression was significantly elevated in serum, BALF and bronchial tissue of the asthmatics, while expression of its protein receptors was reduced. In vitro, activin-A suppressed VEGF-induced endothelial cell proliferation and angiogenesis, inducing autocrine production of anti-angiogenic soluble VEGF receptor (R)1 and interleukin (IL)-18, while reducing production of pro-angiogenic VEGFR2 and IL-17. In parallel, BALF concentrations of soluble VEGFR1 and IL-18 were significantly reduced in severe asthmatics in vivo and inversely correlated with angiogenesis. Activin-A is overexpressed and has anti-angiogenic effects in vitro that are not propagated in vivo, where reduced basal expression of its receptors is observed particularly in severe asthma. Anti-angiogenic role of activin-A, overexpressed in severe asthma, may be compromised by reduced receptor signalling http://ow.ly/W4kxF